Increased Oxidative Stress and Decreased Sirtuin-3 and FOXO3 Expression Following Carotid Artery Intimal Injury in Hyperlipidemic Yucatan Microswine - Velpuri, Prathosh; Patel, Parth; Yazdani, Armand; Abdi, Arian; Rai, Vikrant; Agrawal, Devendra K. (Cardiology and Cardiovascular Medicine, 2024)
Hypercholesterolemia is a major risk factor for atherosclerosis as oxidized-low-density lipoproteins (ox-LDL) contribute to the formation of foam cells and inflammation. Increased immune cell infiltration and oxidative stress induce instability of a plaque. Rupture of the unstable plaque precipitates adverse ischemic events. Since reactive oxygen species (ROS) play a critical role in plaque formation and vulnerability, regulating ROS generation may have therapeutic potential. Sirtuins, specifically sirtuin-3 (SIRT3), are antigenic molecules that can reduce oxidative stress by reducing mitochondrial ROS production through epigenetic modulation. Lack of SIRT3 expression is associated with dysregulation of ROS and endothelial function following high-fat high-cholesterol diet. SIRT3 deacetylates FOXO3a (Forkhead transcription factor O subfamily member 3a) and protects mitochondria against oxidative stress which can lead to even further protective anti-oxidizing properties. This study was designed to investigate the association between hyperlipidemia, intimal injury, chronic inflammation, and the expression of NAD-dependent deacetylase SIRT-3, FOXO3, antioxidant genes, and oxidative stress in carotid arteries of hypercholesterolemic Yucatan microswine. We found that intimal injury in hypercholesterolemic state led to increased expression of oxidative stress, inflammation, neointimal hyperplasia, and plaque size and vulnerability, while decreasing anti-oxidative regulatory genes and mediators. The findings suggest that targeting the SIRT3-FOXO3aoxidative stress pathway will have therapeutic significance.